Single sessions of transcranial direct current stimulation and transcranial random noise stimulation exert no effect on sleepiness in patients with narcolepsy and idiopathic hypersomnia - Hohenester, Michaela; Langguth, Berthold; Wetter, Thomas Christian; Geisler, Peter; Schecklmann, Martin; Reissmann, Andreas (Frontiers in Psychiatry, 2023)
Background: Hypersomnia poses major challenges to treatment providers given the limitations of available treatment options. In this context, the application of non-invasive brain stimulation techniques such as transcranial electrical stimulation (tES) may open up new avenues to effective treatment. Preliminary evidence suggests both acute and longer-lasting positive effects of transcranial direct current stimulation (tDCS) on vigilance and sleepiness in hypersomniac patients. Based on these findings, the present study sought to investigate short-term effects of single sessions of tDCS and transcranial random noise stimulation (tRNS) on sleepiness in persons suffering from hypersomnia.Methods: A sample of 29 patients suffering from narcolepsy or idiopathic hypersomnia (IH) was recruited from the Regensburg Sleep Disorder Center and underwent single sessions of tES (anodal tDCS, tRNS, sham) over the left and right dorsolateral prefrontal cortex on three consecutive days in a double-blind, sham-controlled, pseudorandomized crossover trial. The primary study endpoint was the mean reaction time measured by the Psychomotor Vigilance Task (PVT) before and directly after the daily tES sessions. Secondary endpoints were additional PVT outcome metrics as well as subjective outcome parameters (e.g. Karolinska Sleepiness Scale; KSS). This is a provisional file, not the final typeset article Results: There were no significant treatment effects neither on objective (i.e. PVT) nor on subjective indicators of sleepiness.We could not demonstrate any clinically relevant effects of single sessions of tDCS or tRNS on objective or subjective measures of sleepiness in patients with hypersomnia. However, we cannot exclude that repeated sessions of tES may affect vigilance or sleepiness in hypersomniac patients.